530Extracellular ATP induces atherosclerosis and vascular inflammation via purinergic receptor 2 (P2Y2) in mice. (15th July 2014) - Stachon, P; Peikert, A; Michel, A; Wolf, D; Hoppe, N; Dufner, B; Bode, C; Idzko, M; Zirlik, A
Abstract: Introduction: A solid body of basic evidence support a role for extracellular ATP and its receptors as danger signals in various chronic inflammatory diseases including asthma, chronic obstructive pulmonary disease (COPD), arthritis, allergic dermatitis, graft versus host disease and other entities. The ATP- binding P2Y2- receptor is involved in inflammatory cell recruitment and chronic inflammatory diseases like COPD. Hypothesis: Atherosclerosis represents a chronic inflammatory disease and several lines of evidence suggest that extracellular ATP and the P2Y2- receptor may contribute to atherogenesis. Methods: The expression of P2Y2 was determinded by realtime PCR and immune histology in aortas after feeding LDLR- deficient mice (LDLR-/-) a high (HCD) or low (LCD) cholesterol diet for 16 weeks. To gain into the functional role of extracellular ATP in atherogenesis, LDLR-/- mice on HCD for 18 weeks received either ATP or PBS intraperitoneally 3 times per week. Furthermore, P2Y2 knockout mice (P2Y2-/-) were crossed with LDLR-/- and fed a HCD for 18 weeks. LDLR-/- served as control group. Atherosclerosis was determined histologically. To evaluate the role of ATP and P2Y2 in vascular inflammation, intravital microscopy was performed in P2Y2-/- and LDLR-/- mice stimulated with ATP or vehicle. Results: P2Y2 is overexpressed in murine atherosclerotic aortas compared to healthy vessels indicating a relevant role in atherosclerosis. Stimulation of the P2Y2- receptor by ATP increases atherosclerotic lesions in aortic arches (N=15, control: 0.30mm 2, ATP- group: 0.35 mm 2, p=0.04) and abdominal aortas (N=15, control: 0, 0.34mm 2, ATP- group: 0.18mm 2, p<0.01) significantly. However, the knockout of the ATP- binding P2Y2- receptor reduces atherosclerosis in aortic arches compared to the LDLR-/- control group (N= 10, LDLR-/- :0.26mm 2, P2Y2-/-/LDLR-/-: 0.14mm 2, p = 0.03). Since leukocyte recruitment to the vessel wall is the crucial step in atherogenesis, we examined ATP and its P2Y2- receptor in vascular inflammation. Stimulating mice with ATP intraperitoneally induces leukocyte adhesion and rolling in wildtype mice. In P2Y2-/- mice this effect of ATP is reduced indicating a relevant role of P2Y2 in ATP dependent vascular inflammation. Conclusion: Extracellular ATP acts as a danger signal in vascular inflammation and induces atherosclerosis in mice via purinergic receptor 2. The ATP- P2Y2 axis represents a potential new pathway in pathogenesis of atherosclerosis.